The The Factors that Affect the Implementation of Remote English Teaching: Senior High School Teacher’s and Student’s Perspectives - Sushmita Maheswari; Kadek Sintya Dewi (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Vovid-19 disease causes many problems in various fields. One of them is education. Teachers must be more creative and innovative in teaching. Therefore, teachers can use remote teaching in learning English. This study aims at analyzing the factors that affect the implementation of remote teaching, as well as the description of teachers’ and students’ perceptions of those factors that affect the implementation of remote teaching. The method used is mixed methods and is used as a research design in collecting and analyzing data. The type of mixed methods used is a mixed method which is dominant using qualitative methods compared to quantitative methods. Data were collected by using an interview guide, matrix literature review, and questionnaire. The data analyses using quantitative methods. The results of the study show that there are 10 supporting factors and 9 limiting factors that affect the implementation of remote teaching and another result is the high perception of teachers and students towards these factors. All students majoring in language have positive perceptions and agree with all supporting and limiting factors of remote teaching. Students also agree that the nine limiting factors can be inhibitors during the implementation of the remote teaching process.